Improving students’ achievement in chemistry: comparative effectiveness of conceptual modelling and conceptual blending - Blessing, Edah Ngozi; Urhievwejire, Agboro-Eravwoke Ochuko; Ehighae, Iyayi Innocent; Oghenewede, Ovuworie Onoriode; Faith, Okose; Obro, Sunday (Intelektual Pustaka Media Utama, 2026)
The study looked at how conceptual modelling (CM) and conceptual blending (CB) affected students’ achievement in chemistry. This study employed a quasi-experimental design. In this study, 274 seniors secondary (SSII) chemistry students from six coeducational secondary schools in the state were randomly selected using simple random sampling. The information was gathered using the chemistry achievement test (CAT). It was used for pre-test and post-test to evaluate students’ achievement in chemistry. All groups received these tests before and after a six-week course of therapy. The mean/average scores of the 3 groups on the pre-test and post-test were compared using analysis of covariance (ANCOVA) of the CAT data. The study discovered that CM, as opposed to CB, had a significantly bigger effect on students’ achievement in chemistry. Chemistry achievement was significantly higher with CB than with the lecture approach (LA). According to the study, when compared to the LA, CM and CB are more effective teaching strategies for raising students’ achievement in chemistry. Furthermore, it was discovered that CM was the most successful approach. It was suggested, among other things, that chemistry instructors incorporate CM into their chemical lessons.